Pengaruh Penerapan Metode Pembelajaran EPA (Eksplorasi, Pengenalan Konsep, Dan Aplikasi Konsep) Terhadap Hasil Belajar Peserta Didik Kelas VIII Pada Materi Sistem Pernapasan - Hasniati; Marjuni; Zulkarnaim (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to (1) find out the learning outcomes of students using the EPA learning method, (2) find out the learning outcomes of students using conventional methods, (3) and find out the influence of the application of the EPA learning method on student learning outcomes. This type of research is a pseudo-experiment and research design using nonequivalent control group design. The population in this study was 61 students from all students of class VIII MTs Muhammadiyah Datarang. The study sample was 21 students of class VIII A and 21 students of class VIII B who were selected by purposive sampling technique. The research instrument used to measure learning outcomes is a learning outcomes test in the form of a multiple choice test of 15 numbers. Data analysis techniques use descriptive data analysis and inferential data analysis. The results showed that students in the experimental class had an average learning outcome of 79.61, while in the control class it was 59.5. The t-test results obtained a sign value for learning outcomes of 0.000, this value shows that the sign < α = 0.000 < 0.05 so that H0 is rejected and H1 is accepted, which means that there is a significant difference between the experimental class and the control class, and the experimental class using the EPA method is better than the control class using conventional methods.